« Un studio à soi ». Entrevue avec Bérengère Marin Dubuard, du Studio XX - Parent, Sylvie (ETC, 2008)
Un article de la revue ETC, diffusée par la plateforme Érudit.
Publisher: Revue d'art contemporain ETC inc.

Considering Complexity in Canadian Civil Society: A Case Study of Studio XX - Gerlach, Neil; Hamilton, Sheryl (Revista Mexicana de Estudios Canadienses, 2002)

Virtually Civil: Studio XX, Feminist Voices, and Digital Technology in Canadian Civil Society - Gerlach, Neil; Hamilton, Sheryl N. (Civic Discourse and Cultural Politics in Canada, 2002)